Augmented Pokemon Go in Times of Covid-19: Does it Have any Effect on Promoting Teenagers' Physical Activity? - Hasanuddin Jumareng; Edi Setiawan; Zsolt Németh (OVS LLC, 2022)
Study purpose. One of the main problems during the COVID-19 pandemic that needs to be considered is the decline in physical activity carried out by teenagers. The overall objective of this mixed method is to investigate the effects of the Pokemon Go intervention program to promote physical activity in teenagers during the COVID-19 crisis. Materials and methods. This study was conducted through a mixed method approach. 94 teenagers in grades 10-12 from three high schools agreed to participate in this study. The subjects were divided into 2 groups, namely in the Pokemon Go intervention program group (N=47) and a control group that did not get any physical activity (N=47). The Pokemon Go intervention program was carried out for 7 weeks with an intensity of 3 times a week in physical education classes. After carrying out the Pokemon Go intervention program, the forty-seven subjects were interviewed. The quantitative instrument used to measure the physical activity level was IPAQ, while the qualitative instrument used in-depth interviews. Results. The quantitative and qualitative (mixed) research confirms that the Pokemon Go intervention program showed to positively promote PA levels in teenagers to higher levels in the current COVID-19 crisis. The results of this study are in line with the previous studies which explained that Pokemon Go is an augmented reality game that requires players to travel to various locations in the real world where distances are relatively far. Conclusions. Teenagers with the status of players, ex-players and non-players experienced a significant increase in physical activity level after participating the Pokemon Go intervention program for 7 weeks, and the majority of subjects considered that Pokemon Go had a positive effect to promote physical activity during the COVID-19 pandemic. After implementing the Pokemon Go intervention program for 7 weeks, the results of our study confirm that the physical activity levels of teenagers have gradually increased during the COVID-19.